1歳児の下顎骨に生じた小円形細胞腫瘍の1例 - 蔵原, 慎一; 中村, 誠司; 鬼丸, 満穂; 石橋, 浩晃; 佐々木, 匡理; 白砂, 兼光 (日本口腔外科学会雑誌, 2009)
Neuroblastoma, Ewing sarcoma, rhabdomyosarcoma, and malignant lymphoma consist of undifferentiated small round cells with scanty cytoplasm and are classified as so-called small round cell tumors. These tumors are often difficult to distinguish on light microscopy and to make a definitive diagnosis because they have poor histological characteristics. We report a case of a small round cell tumor arising in the mandible of a 1-year 9-month-old girl. She was referred to our department because of swelling in the left side of the mandible in November 2003. Computed tomographic(CT)scans revealed a soft tissue density area expanding buccolingually in the mandible. An incisional biopsy was done under general anesthesia for a suspected diagnosis of an intra-osseous carcinoma of the mandible. A neurogenic malignant tumor was suspected from the biopsy specimen because of CD56 activity. Based on clinical, radiological, and histopathologic findings, a radical resection of the tumor was performed via a submandibular approach in March 2004. Following hemimandibulectomy, primary reconstruction of the defect was performed, using a titanium plate. Because the tumor cells were positive immunohistochemisty for neural markers in the surgical specimen, the definitive diagnosis was a malignant small round cell tumor with nueroendocrine features. Five years after surgery, there has been no evidence of recurrence or metastasis.